2014
DOI: 10.1097/aln.0000000000000401
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Transitions of Anesthesia Care and Postoperative Adverse Outcomes

Abstract: Intraoperative anesthesia care transitions are strongly associated with worse outcomes, with a similar effect size for attendings, residents, and nurse anesthetists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(117 citation statements)
references
References 38 publications
5
107
1
4
Order By: Relevance
“…Hudson et al 1 found a 43% increase of in-hospital mortality and a 27% increase of major morbidity associated with intraoperative handovers between anaesthetists in cardiac surgery. Similar effects were observed by Saager et al 2 in general surgery and by Hyder et al 3 during colorectal surgery.…”
Section: Introductionsupporting
confidence: 85%
“…Hudson et al 1 found a 43% increase of in-hospital mortality and a 27% increase of major morbidity associated with intraoperative handovers between anaesthetists in cardiac surgery. Similar effects were observed by Saager et al 2 in general surgery and by Hyder et al 3 during colorectal surgery.…”
Section: Introductionsupporting
confidence: 85%
“…This was related to the transfer of information between different intra-operative teams prior to the postoperative handover resulting in limited time available to gain knowledge of the patient during surgery. Research on intra-operative handovers describes timing as a risk factor for handovers close to emergence and induction of anaesthesia (Testa & Emery, 2014) as well as linking the number of intra-operative handovers to increased mortality (Saager et al, 2014). Avoiding postoperative handovers with closeness in time to intra-operative handovers is difficult to eliminate, due to the way perioperative care is organised.…”
Section: Preparation and Timing Affects Handover Qualitymentioning
confidence: 99%
“…Fourth, care is more commonly fragmented with many hand-offs and multiple transitions of care throughout the perioperative period [14]. No single provider 'owns' the entire course of care.…”
Section: What Is Wrong With the Current Model(s) Of Care?mentioning
confidence: 99%
“…Similarly, we should build on the experience -both positive and negative with the use of telemedicine in the ICU and emergency department setting as well as other remote monitoring capabilities to identify lessons learned and their application in perioperative management. Finally, we need to identify the ways to improve communication and coordination of all aspects of care [14].…”
Section: Redefining Roles Of Physician and Nonphysician Providers In mentioning
confidence: 99%